Pembinaan Remaja Masjid dalam Mempelajari Al-Quran - Moh. Sain; Asmariani Asmariani; Ahmad Ahmad; Seri Yanti Siagian (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
One of the public concerns at Parit. 17 Sungai Beringin, Tembilahan Sub-district, Indragiri Hilir, the Ar-Rahman Mosque held guidance for learning Al-Quran using the tazkirah method. The guidance of the Al-Quran aimed to make the youth the holder of control in prospering and developing programs that have been designed by the administrators or founders of the previous mosque. The youth are a group of human beings full of potential who need to be guided and directed, without being guided and directed, meaning breaking the chain of relay holders to leaders to function the mosque as a means of da'wah and other places of study of Islamic knowledge.